Muslims and Media Images: News Versus Views By Ather Farouqui, ed. (New York: Oxford UP, 2011. pbk. 368 pages.) (American Journal of Islam and Society, 2012)
Ather Farouqi’s edited book Muslims and Media Images: News VersusViews examines the Hindi and Urdu press as well as Hindi and regional languagefilms. The uniqueness of the collection lies in the grounded approachtaken to study the topic of media images of Indian Muslims. Along with anintroduction and two appendices, this volume consists of nineteen mainlyshort chapters organized in four sections that highlight the experiences ofmedia practitioners, who provide their own accounts and testimonies. Consistingof journalists, newspaper editors, filmmakers, and academics ‒ thecontributors to this volume are writing from the field, while incorporatinghistorical components in a tone embedded in a storytelling style. Althoughcertain generalizations and scattered links between chapters might distractreaders, such grounded conversations are valuable to academics interestedin generating theory from the practice of making media. Most authors providedvivid examples here from their own involvement in the process ofwriting or editing news, while relying on a minimal use of citations, whichpresents an interesting alternative format to standard academic studies.This book offers relevant reading to scholars of Islamic studies, communication,journalism, cinema, political science, and readers interested inIndian media and Muslim representations ...